Domesticating Everyday Technologies for Teaching - Freeman, Wendy (Proceedings of the International Conference on Networked Learning, 2018)
The complexity of technology integration into the teaching and learning practices of higher education students and instructors is not adequately captured in technology adoption models. Technologies are shaped not only by faculty as they integrate these tools into their teaching, but by students in their learning. Studies examining technology integration tend to take the classroom as the beginning and ending point for technology integration; however, beliefs, values, expectations, and experiences of technology begin long before the classroom. This study takes these experiences into account, exploring university faculty understanding of social media for teaching through the lens of domestication theory. Domestication theory (Berker, Harmann, Punie & Ward, 2006; Haddon, 2011; Silverstone & Hirsch, 1992) draws on family studies, media consumption studies and studies of the social construction of technology to examine the confluence of the social meanings and political structures of the home as technology become integrated into domestic practices. This study uses the domestication framework to explore how values, beliefs, and experiences of social media and of teaching shape the decision-making processes of instructors as they integrate these everyday communication platforms into their courses. The domestication framework traces the trajectory of a technology from the point at which it enters the home through the social processes of domestication. The first stage is appropriation, in which the imagined uses for the technology lead someone to bring it home. The dual processes of objectification and incorporation describe the ways in which an individual or a group integrates a new technology into the physical arrangements and everyday routines of the household. It is through these negotiations that values and beliefs about everyday practice and the role of the technology become apparent. Finally, conversion, in which newfound practices and technologies are displayed, begins the process of appropriation for others. Twelve university faculty were interviewed about their decision-making and experiences as they integrated social media into their teaching practices. Participants had varying levels of experience with social media prior to their decision to use social media in their teaching. Analysis using the domestication framework suggests that the everyday experiences with technology outside the classroom affect the approach to integrating new technology into teaching. The domestication framework provided a valuable lens for teasing out the social and material beliefs inherent in the negotiation processes in which both instructors and students engage as technology is introduced into the classroom.